The relationship between header type and head acceleration during heading in male youth football players - Bradbery, E.; Cairns, R.; Peek, K. (Physical Therapy in Sport, 2024)
Objective To explore head impact magnitude (linear head acceleration and rotational velocity) during heading for four different header types in youth male footballers. A secondary objective was to explore whether head impact magnitude was influenced by player-related factors (i.e. age, neck strength).